Identification and characterization of the Remorin gene family in Saccharum and the involvement of ScREM1.5e-1/-2 in SCMV infection on sugarcane - Yang, Zongtao; Cheng, Guangyuan; Yu, Quanxin; Jiao, Wendi; Zeng, Kang; Luo, Tingxu; Zhang, Hai; Shang, Heyang; Huang, Guoqiang; Wang, Fengji; Guo, Ying; Xu, Jingsheng (Frontiers in Plant Science, 2024)
Introduction Remorins (REMs) are plant-specific membrane-associated proteins that play important roles in plant–pathogen interactions and environmental adaptations. Group I REMs are extensively involved in virus infection. However, little is known about the REM gene family in sugarcane (Saccharum spp. hyrid), the most important sugar and energy crop around world. Methods Comparative genomics were employed to analyze the REM gene family in Saccharum spontaneum. Transcriptomics or RT-qPCR were used to analyze their expression files in different development stages or tissues under different treatments. Yeast two hybrid, bimolecular fluorescence complementation and co-immunoprecipitation assays were applied to investigate the protein interaction. Results In this study, 65 REMs were identified from Saccharum spontaneum genome and classified into six groups based on phylogenetic tree analysis. These REMs contain multiple cis-elements associated with growth, development, hormone and stress response. Expression profiling revealed that among different SsREMs with variable expression levels in different developmental stages or different tissues. A pair of alleles, ScREM1.5e-1/-2, were isolated from the sugarcane cultivar ROC22. ScREM1.5e-1/-2 were highly expressed in leaves, with the former expressed at significantly higher levels than the latter. Their expression was induced by treatment with H2O2, ABA, ethylene, brassinosteroid, SA or MeJA, and varied upon Sugarcane mosaic virus (SCMV) infection. ScREM1.5e-1 was localized to the plasma membrane (PM), while ScREM1.5e-2 was localized to the cytoplasm or nucleus. ScREM1.5e-1/-2 can self-interact and interact with each other, and interact with VPgs from SCMV, Sorghum mosaic virus, or Sugarcane streak mosaic virus. The interactions with VPgs relocated ScREM1.5e-1 from the PM to the cytoplasm. Discussion These results reveal the origin, distribution and evolution of the REM gene family in sugarcane and may shed light on engineering sugarcane resistance against sugarcane mosaic pathogens.